2015
DOI: 10.1111/jcpp.12509
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based cognitive behavioural psychotherapy for children and adolescents with ASD: the randomized, multicentre, controlled SOSTA – net trial

Abstract: Short-term ASD-specific add-on group-based psychotherapy has shown postintervention efficacy with regard to parent-rated social responsiveness predominantly in male high-functioning children and adolescents with ASD. Future studies should implement blinded standardized observational measures of peer-related social interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 33 publications
6
70
1
Order By: Relevance
“…Looking at changes in parent‐rated ASD behavior (assessed using the SRS) we saw stronger reduction in SRS scores in the intervention‐ compared to the TAU‐group, with a similar effect size as reported in the large scale RCT of the SOSTA‐FRA intervention [Freitag et al, ]. No nominal statistical significance could be established due to the small sample size of the present subsample, which was insufficient to detect the low to medium effect shown in the RCT.…”
Section: Discussionsupporting
confidence: 80%
“…Looking at changes in parent‐rated ASD behavior (assessed using the SRS) we saw stronger reduction in SRS scores in the intervention‐ compared to the TAU‐group, with a similar effect size as reported in the large scale RCT of the SOSTA‐FRA intervention [Freitag et al, ]. No nominal statistical significance could be established due to the small sample size of the present subsample, which was insufficient to detect the low to medium effect shown in the RCT.…”
Section: Discussionsupporting
confidence: 80%
“…A search of the current literature evaluating SSGTs for adolescents via randomized controlled trials (RCTs), identified a number of design and intervention limitations. Consistent design limitations included small sample sizes (9,(27)(28)(29)(30)(31), failing to employ blinded or external observer-report measurement of dependent variables (17,20,27,29,30,(32)(33)(34)(35), failing to describe the randomization processes (27, 29-31, 33, 34) or employ allocation concealment (17,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), limited application of intent-to-treat data analysis (17,(27)(28)(29)(30)(32)(33)(34)(35), a lack of clarity in regard to compliance with the Consolidated Standards of Reporting Trials (CONSORT) statement (20,27,29,30,35,36), and limited examples of mixed methods studies integrating quantitative and qualitative data collection methods and analysis in understanding the outcomes of interventions…”
Section: Social Skills Group Trainingmentioning
confidence: 99%
“…A range of identified intervention shortcomings included limited consideration or incorporation of adolescents' personal goals (20, 27-31, 33, 34, 36), outcomes largely measured by parent proxy report (17,28,29,31,32,35,36), inadequate tailoring of interventions to individual activity preferences (20,29,30,(33)(34)(35)(36), failing to consider the relationship between intervention dosage (that is the number of sessions) and outcomes (20,(27)(28)(29)(30)(31)(33)(34)(35)(36), the absence of cost analysis (17,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and limited reporting of adverse events during the intervention period (20, 27-30, 32-34, 36) (Additional file 1). While comparison groups varied considerably, most examined the efficacy of SSGT interventions relative to usual care waitlist control groups, with limited description of what interventions and therapies were received by comparison groups.…”
Section: (Additional Files 1 and 2)mentioning
confidence: 99%
“…A number of interventions have been developed and studied to target the social skills of children and adolescents with ASD 2. One particularly promising group intervention, namely the Social Skills Training Autism—Frankfurt (SOSTA-FRA),3 targets social motivation, social cognition, self-regulation and peer interaction using cognitive-behavioural treatment techniques provided using multiple methods (ie, social learning, computer-based, behavioural, cognitive methods) within a structured framework. Preliminary data have shown promising treatment effects and acceptability; further study in a controlled setting is necessary.…”
Section: What Is Already Known About This Topic?mentioning
confidence: 99%